Isolation And Characterization Of Hypervariable Region (HVR II) From Cellulose Synthase Gene In Neolamarckia Macrophylla - Chang, C.N; Ho, W.S; Pang, S.L (IJSTR, 2014)
The present study is aimed to isolate and characterize the hypervariable (HVRII) region in cellulose synthase gene from the developing xylem tissues of a tropical timber tree species, Neolamarckia macrophylla. N. macrophylla is locally known as red kelampayan and it has been selected as one of the important reforestation tree species in Malaysia. RT-PCR was carried out by using the degenerate primers and one of the three amplified DNA bands was successfully sequenced and characterized. The sequence was named as NmCesA1HVRII and it was clustered in a distinct clade that is associated with secondary cell wall development. This study has generated a useful genomic resource for a better understanding about the HVRII region of CesA gene in N. macrophylla and its function which is important in future applications, genetic improvement of N. macrophylla. This also facilitates the future selection of trees with optimal cellulose content required for certain specific industries as well as synthesizing of artificial cellulose, hence increasing the economic development and growth in the country.